Frequency of metabolic syndrome among newly detected type 2 diabetic patients with non-alcoholic fatty liver disease and high serum alanine aminotransferase levels (BIRDEM Medical Journal, 2019)
Background: Non-alcoholic fatty liver disease (NAFLD) is emerging as one of the most common causes of chronic liver disease world-wide. It has strong association with obesity, type 2 diabetes mellitus (T2DM) and metabolic syndrome. We aimed to investigate the prevalence of metabolic syndrome in newly detected T2DM patients having NAFLD with high serum alanine aminotransferase (ALT) level.Methods: In this cross-sectional study, 110 newly detected T2DM patients with high serum ALT level were evaluated. To find out the etiology of high serum ALT level, abdominal ultrasonography was done to detect NAFLD cases along with other relevant investigations. All NAFLD cases then underwent further evaluation for the prevalence of metabolic syndrome.Results: Out of 110 study subjects, NAFLD was detected in 80 (72.7%) individuals. According to International Diabetic Federation (IDF) criteria, metabolic syndrome was detected in 56 (56/80, 70%) of NAFLD cases. Among the 56 patients with NAFLD, male were 24 (42.9%) and female were 32 (57.1%) and 14 (14/56, 25%) cases had all five components of metabolic syndrome. Metabolic syndrome was found in all female NAFLD subjects (32, 100%). Mean age of patients with metabolic syndrome was 43.11±10.77 years and mean body mass index (BMI) was 27.87±3.72 kg/m2. Hypertension was found in 37.5% cases. High BMI (e”25 kg/m2) was found in 87.5% cases. Mild, moderate and severe fatty liver were found in 28.6%, 46.4% and 25% cases respectively. Dyslipidemia was found in all (56, 100%) NAFLD subjects with metabolic syndrome. Metabolic syndrome had significant correlation with BMI (p 0.00), abdominal obesity (p 0.00) and serum triglyceride level (p 0.04).Conclusion: Over two-thirds of T2DM patients having NAFLD had metabolic syndrome in this study.Birdem Med J 2020; 10(1): 21-25